Pollution Risk Assessment of Heavy Metals in Paradgaon Lake Sediments, Central India - Sonal D. Kamble; Sumedh K. Humane; Samaya S. Humane; Pranit Gajbhiye; Dileep Abdul Kalam T.; Snehal Juare (Indonesian Journal on Geoscience, 2026)
The assessment of heavy metal contamination is pivotal in understanding environmental health and its impacts on aquatic ecosystems. This study aims to assess the concentration and distribution of heavy metals in the sediments of The Paradgaon Lake (PL) of Umrer Taluka, Maharashtra State, India, and to evaluate the level of pollution and ecological risks using various pollution indices. Six surface sediment samples (three each during pre and post monsoon seasons) along with five soil samples were collected from the PL and surrounding locations, respectively in the catchment of the PL. The air-dried powdered sediment samples were analyzed for the heavy metal concentrations using X-Ray Fluroscence (XRF) Spectrometry. The present study investigates the contamination of the heavy metals such as iron (Fe), aluminium (Al), manganese (Mn), zinc (Zn), copper (Cu), chromium (Cr), nickel (Ni), lead (Pb), cobalt (Co), uranium (U), vanidium (V), and rubidium (Rb). The appraisal of sediment contamination was analyzed on the basis of enrichment factor (EF), Geo-accumulation Index (GI), Contamination Factor (CF), and Pollution Load Index (PLI). Additionally, ecological risk factor (Er) and potential ecological risk index (PERI) were calculated to comprehend the toxicity of heavy metals and the environmental response to all risk factors. The key metal contaminants in lake surface sediments include Fe, Al, Zn, Mn, Cr and Co. This study demonstrates that these heavy metals were generated from the common lithogenic source generated through weathering and erosion of the Deccan Trap Basalt (DTB) and associated soils in the catchment in addition to partial input from the adjoining coal mining. The heavy metals such as Zn, Cu, Cr, Ni, Pb, U, and Rb showed their higher concentrations during the premonsoon (PM) season as compared to the postmon-soon (PoM), while metals like Al, Fe, Mn, Co, and V have increased concentrations during the PoM season, indicating enhanced weathering and erosion in the different parts of the rocks (DTB) and associated soils contributing these metals during the monsoonal season in the catchment of the PL. The geoaccumulation index and contamination factor of the heavy metals in the PL showed moderate pollution level. These metals may be originated from anthropogenic sources such as agricultural runoff and coal mining in addition to natural geological processes. Overall, the study on Igeo, CF reflects moderate level of pollution, whereas the EF and Er clearly signifies the changes in land-use type and rainfall patterns on heavy metal accumulation in the present lake. The strong positive correlation between Mn and total organic carbon (TOC) points their biogenic source, while Pb has high positive correlation with total inorganic carbon (TIC) and moderately correlated with TOC indicating mainly anthropogenic origin of Pb with its input from coal mine and deposited in the soils of the catchment of the PL. The present findings also provide valuable insights of the environmental risk of heavy metals pollution in the Paradgaon Lake.